METACARBONATE ROCKS (CALCIPHYRES) OF THE LAPLAND-KOLVITSA GRANULITE BELT, BALTIC SHIELD - Safronov V.T.; Rosen O.M. (My University, 2004)
Geological, petrochemical, and geochemical data are presented on metacarbonate rocks (calciphyres) of the Lapland—Kolvitsa granulite belt, Baltic Shield. The normative mineral composition of source rocks of the studied calciphyres was first reconstructed. High contents of some indicator elements (Fe, Mn, Cr, Co, P, Pb, and others) suggest that material supplied to the paleobasin was derived from diverse rocks (ultramafic, mafic, intermediate, and felsic). Contents and correlations of some trace elements (Sr, Li, F, Ba, and others) indicate that primary sediments formed under humid-semihumid paleoclimate in a fresh-water paleobasin (lagoon) characterized by occasional increase in salinity.